LOADING AND CARGO SECURING DEVICES IN STANDARD FORTY FOOT GENERAL PURPOSE MARITIME CONTAINERS - Jagelcak, Juraj; Vrabel, Jan; Fazekas, Miroslav (Doprava a spoje, 2011)
The maritime container is cargo transport unit used all over the world. The cargo must be appropriately secured during the carriage to withstand normal transport conditions during road, rail and sea carriage. For such securing container structures and securing devices are used. The paper shows the results of analysis of cargo securing equipment in fourty foot general purpose maritime containers of various shipping lines and leasing companies. The results show a variety of used cargo securing equipment in such containers. Standard ISO 1496-1 in Annex F specifies only general requirements for such equipment not specifying where this securing equipment must be placed. More specific is standard EN 12640 but this standard specifies lashing points for vehicle superstructures only.